Interlanguage and its Implications in L2 Teaching - Qingxue, Liu (Investigationes Linguisticae, 2002)
Recent research has shown that adult students learning a second or foreign language generally form a systematic interlanguage grammar which is influenced by both the mother tongue and the target language and has features of each. This interlanguage continues to approximate and improve in the process of the learner’s second language acquisition towards the final internalization of the target language system. In this paper, the author introduces the Interlanuage Hypothesis, analyses its nature and mainly based on the cases of the Chinese adult learners of English, explores the specific characteristics of the interlanguage grammar - its phonology, morphology, syntax and semantics. Towards the end of the paper the author also points out some implications the Interlanguage research might have on the practical fields of our contemporary second language teaching and learning.